MUC481 : Melodic and harmony writing / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
This course exposes students to the fundamentals of composition. Students will learn the basic techniques of writing an original melody with chord patterns. Applying these techniques students will be able to develop melodic ideas over different styles of music.